Successful Recanalization by Mechanical Thrombectomy in a Child with Arterial Thrombotic Stroke Involving Posterior Circulation: A Case Report with Review of the Literature - Aanchal Mangal; Neeraj Bhutani; D. P. Sharma (Wolters Kluwer Medknow Publications, 2024)
Background: Mechanical thrombectomy (MT) for arterial ischemic stroke, although established in adults, is not endorsed routinely for children. The procedure is even rare in children with stroke involving posterior circulation. Here we describe, a child with ischemic stroke due to thrombotic occlusion in the posterior circulation, which was successfully treated with MT. Clinical Description: A 12-year-old boy presented with sudden-onset vertigo, imbalance, slurring of speech, inability to stand, associated with headache and vomiting for 8 hours, without any associated fever, trauma, or seizures. On initial examination, his National Institute of Health Stroke Scale (NIHSS) score was 8. Other systems were within normal limits and there was no cutaneous rash. Management and Outcome: Investigations revealed a normal complete hemogram, lipid profile, serum homocysteine, fibrinogen, and D-dimer levels along with a normal hemoglobin electrophoresis profile. The electrocardiography, two-dimensional echocardiography were normal and even antinuclear antibodies, antiphospholipid antibodies were negative. Magnetic resonance imaging (MRI) of the brain demonstrated multiple acute infarcts in bilateral cerebellar hemispheres, pons, and right anterior thalamus. Noncontrast MR angiography (MRA) of the head and digital subtraction angiography showed distal basilar artery cutoff and right vertebral artery dominance. As the NIHSS score worsened to 10, a MT with solitaire was done (after 12 hours of onset of symptoms), and reperfusion was achieved in two passes. The child showed remarkable improvement in NIHSS score to 2 by 5 days. At discharge, the child had residual mild ataxia. Despite investigations, the cause of thrombosis remained unknown. Conclusion: Our case highlights that in case of significant large arterial occlusion with rapid worsening of symptoms, MT may be considered, even if it involves posterior circulation, and the child presents beyond the usual window of 4-6 hours.